La mia distanza dalle stelle Utopia e distopia nel canzoniere di Fabrizio De André - Cannas, Andrea (La biblioteca di Medea, 2022)
The book engages with the dense literary substratum that nourishes the work of singer-songwriter Fabrizio De André in order to bring out the unmistakable stylistic trait and the operational methods in which the writing of a great narrator in verses finds full expression.